The detection of residual gasoline for forensic soil investigation in arson - Cheenmatchaya A. (2017)
© 2016 Australian Academy of Forensic Sciences The cause of an arson fire is difficult to investigate. Detection of gasoline residue can provide important information to link evidence with an arson scene. Soil can be taken as physical evidence from an arson scene and also used to indicate the presence of gasoline residue. Since each soil has different characterisation details, this study was undertaken to present an effective method for soil sampling. Gasoline permeability in soil is affected by soil type. This study investigates the permeation of gasoline into four different soil types and determines the optimum soil depth for gasoline detection. The effect of burning duration and the time between extinguishing the fire and taking the sample were also investigated. The studied soils were collected from various soil series in Thai Northern region. The results indicate that soil structure, burning duration and sampling period are important factors that have a significant effect on residual gasoline detection in each of the soil series studied. The key finding of this study was that the optimum depth for all studied soil series was 5 cm below the surface. These findings have implications for crime scene investigators carrying out soil evidence investigation at an arson scene.